Utilizing Telemedicine During Outbreak Events to Reduce Exposure Risk. (October 2020) - Bisht, Anjali; Weinstein, Stacey; Uslan, Daniel
Abstract : Background: As of October 2019, the United States has seen the greatest number of annual measles cases reported since 1992, of which 2 outbreaks originated in Los Angeles County, California. Media reports and public awareness during outbreak events can result in large numbers of worried well patients or patients with outbreak mimics seeking medical attention. In densely populated cities, utilizing alternative approaches to in-person physician appointments can be beneficial to decrease both the overburden of healthcare resources as well as the spread of potential virus. During these measles outbreaks, we employed the use of telemedicine visits to facilitate triage and determination of in-person examination and testing needs. Methods: During the measles outbreak periods, patients who contacted the patient call center at our institution requesting an appointment for fever, rash, or expressing concerns for acute measles infection were instead routed for a telemedicine visit with a physician. All patients were all seen by the same physician, who was trained in internal medicine and pediatrics. During the telemedicine visit, patients were assessed for signs and symptoms consistent with acute measles based on CDC definition. If there was high enough clinical suspicion to warrant testing for measles, infection prevention coordinated logistics with clinic staff, including ensuring the use of appropriate personal protective equipment (PPE), end-of-day appointment scheduling, and appropriate diagnostic testing. Results: During this outbreak timeline, 7 patients were seen through telemedicine visits with ages ranging 13 months to 49 years. Also, 6 patients were scheduled due to a chief complaint of acute rash and 1 was due to a potential exposure to measles. Of 7 patients, 4 had received 1 dose of the MMR vaccine, and the remaining 3 were immune, unvaccinated, or had unknown immunity. The unvaccinated patient was further tested for measles but was IgM negative. Of those with chief complaint of rash, the diagnosis was determined to be some form of nonmeasles viral exanthem, allergic dermatitis/eczema, or hives. The exposed patient was deemed to be asymptomatic. Conclusions: During an outbreak, patients presenting to clinics with suspected measles symptoms can cause tremendous disruption, including concerns about exposure of staff and patients, need for contact tracing, and anxiety. Utilizing telemedicine appointments aided the management of patients during this outbreak by shifting physician evaluation outside the clinic. When evaluating suspect measles cases during an outbreak with patients who do not require further levels of care, telemedicine can prove to be useful in reducing the burden of potential exposure to others in the community and to the healthcare system. Funding: None Disclosures: None